KELEMBAGAAN POKMASWAS: EVALUASI PERAN AKTIF DALAM PENGAWASAN SUMBER DAYA PERIKANAN DAN KELAUTAN DI KECAMATAN PULAU HARUKU - Revalda A Y B Salakory; Yoisye Lopulalan (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2026)
The high level of vulnerability to destructive fishing practices in Haruku Island indicates that the monitoring and surveillance of marine and fisheries resources have not yet been optimally implemented. In this context, community involvement plays a strategic role in supporting effective monitoring efforts, which are institutionalized through the establishment of Community Based Surveillance Groups (Pokmaswas). The extent of Pokmaswas’ institutional involvement can be assessed through an evaluation of their active role in the monitoring of marine and fisheries resources. This study employed a mixed methods approach, with data analyzed using descriptive methods and the Activity Index (AI). The results indicate that Pokmaswas in Haruku Island District fall into the very active category in carrying out their roles, particularly in participating in socialization and capacity-building activities conducted by relevant agencies, with an Activity Index score of 78.18%. The Pokmaswas groups with the highest level of activity were Pelasona and Hasroka, with average Activity Index scores of 92.36% and 91.37%, respectively, both of which are categorized as very active. Therefore, integrated cooperation among relevant stakeholders including central and local governments as well as non governmental organizations (NGOs) is necessary in the implementation of guidance and education programs, technical training, provision of supporting facilities and infrastructure, and the awarding of incentives or rewards to high-performing Pokmaswas, with requirements and conditions that are easy to fulfill.